Self-censorship in using social media in Bangladesh: Does regime structure matter? - Sabrina Nughat (Goodwood Publishing, 2024)
influences social media users' self-censorship by examining how repression, legal frameworks, surveillance, and media control affect online expression and free speech. Method: This study on self-censorship in Bangladesh used interviews, content analysis, focus groups, and surveys to understand users' online behavior under a hybrid regime. The results showed that laws such as the Digital Security Act increased self-regulation. Results: The study revealed that regime structure significantly impacts self-censorship on social media in Bangladesh. Democratic environments reduce self-censorship, whereas restrictive regimes increase it. Higher educational levels are associated with greater self-censorship, likely due to heightened awareness of the consequences. Gender and government actions had a minimal impact. An interaction effect demonstrates that a